The mediating effect of sustainable consumption attitude on association between perception of sustainable lifestyle and sustainable consumption practice - Zakaria, Nurul Fardini; Abdul Rahim @ Abdul Wahab, Husniyah; Paim, Laily; Zakaria, Nurul Farhana (Canadian Center of Science and Education, 2019)
The issue of sustainability is increasingly becoming the focus of research activities. In order to achieve sustainability, various parties need to play their role, including the adolescents. However, environmental issues appear to be more critical nowadays. The aim of this study was to determine the relationship between the perception of sustainable lifestyle and sustainable consumption practice among urban adolescents in Selangor, Malaysia. The Structural Equation Modelling analysis was able to measure the impact of mediator sustainable consumption attitude on the relationship between perception of sustainable lifestyle and sustainable consumption practice. Finding of the study showed that sustainable consumption attitude is a partial mediator of the relationship between perception of sustainable lifestyle and sustainable consumption practice. Through this study, factors affecting sustainable consumption practice among adolescents can be identified in detail, subsequently can be used as input in the implementation of sustainable consumption practice programs to help adolescents practice sustainable consumption.